The Influence of Coronal Mass Ejections on the Mass-loss Rates of Hot-Jupiters - Cherenkov, A.; Bisikalo, D.; Fossati, L.; Möstl, C. (The Astrophysical journal, 2017)
Hot-Jupiters are subject to extreme radiation and plasma flows coming from their host stars. Past ultraviolet Hubble Space Telescope observations, supported by hydrodynamic models, confirmed that these factors lead to the formation of an extended envelope, part of which lies beyond the Roche lobe. We use gas-dynamic simulations to study the impact of time variations in the parameters of the stellar wind, namely that of coronal mass ejections (CMEs), on the envelope of the typical hot-Jupiter HD 209458b. We consider three CMEs characterized by different velocities and densities, taking their parameters from typical CMEs observed for the Sun. The perturbations in the ram-pressure of the stellar wind during the passage of each CME tear off most of the envelope that is located beyond the Roche lobe. This leads to a substantial increase of the mass-loss rates during the interaction with the CME. We find that the mass lost by the planet during the whole crossing of a CME is of 1015 g, regardless of the CME taken into consideration. We also find that over the course of 1 Gyr, the mass lost by the planet because of CME impacts is comparable to that lost because of high-energy stellar irradiation.